Treatment of stable partial cruciate rupture (Grade 1 sprain) in five dogs with tibial plateau levelling osteotomy. Issue 1 (13th July 2016) - Barger, B; Piazza, A; Muir, P
Abstract : Tibial plateau levelling osteotomy (TPLO) is increasingly being used for treatment of stable partial cruciate ligament rupture (CR) in dogs. Medical records for TPLO‐treated dogs from 2003 to 2014 were reviewed and five cases were identified. Data retrieved included physical examination, diagnostic imaging and treatment. At long‐term follow‐up, the outcome was evaluated by clinical examination, stifle radiographs and force platform gait analysis. The time to follow‐up examination was 892±673 days for six stable stifle TPLO treatments in five dogs. Stifles with partial CR remained cranial drawer and cranial tibial thrust negative at follow‐up, with little progression of stifle osteoarthritis (OA). These observations suggest that TPLO is an effective clinical treatment for dogs with lameness because of partial CR. TPLO treatment reduces cranial cruciate ligament (CrCL) strain, based on ex vivo model studies. Clinically, TPLO may act to block fibre tearing in the CrCL and associated progression of stifle OA in dogs with partial CR.